The Effect of the Ban on Nickel Exports on the Economic Profitability of PT Vale Indonesia, Tbk from 2015 - June 2020. - Situmorang, Humala (Universitas Kristen Indonesia, 2021)
The purpose of this study was to determine the effect of government policies to prohibit the export of raw materials for mining ore, especially nickel ore, to foreign countries based on Permen ESDM No. 01/2014 on the economic profitability of INCO companies from 2015 to June 2020. To see the company's economic profitability, it can be seen from the side of gross profit margin, net profit margin, return on assets, and return on equity. This analysis is made by compiling profitability ratios in one table so that it is expected to provide clearer information for interested parties. INCO Tbk is a mining company listed on the Indonesia Stock Exchange whose majority shares are owned by foreign countries. From the results of the research and analysis that has been carried out, it can be concluded that the ban on nickel ore exports has a negative effect on gross profit margin, net profit margin, return on assets, and return on equity from 2015-2017, but the ban on nickel ore exports has no negative effect. on gross profit margin, net profit margin, return on assets, and return on equity from 2018-June 2020. Keywords: economic profitability, gross profit margin, net profit margin, return on assets, and return on equity, exports.